Clarification of colloidal particles in lake and river water using AC Electrokinetic - Mohtar, Mohd Nazim; Ramli, Muhammad Mahyiddin; Md Yunus, Nurul Amziah; Jasni, Jasronita; Aziz, N. (EDP Sciences, 2016)
Scenery of clear water of a lake or river is always a fascinating view. The clarity of a water is subjected to the water free from colloidal particles. Lake or river usually have foreign colloidal particles such as sand, mud, foreign particle, etc. which make the water cloudy. Usually the cloudy water become clear because of natural sedimentation process. However it is not easy to clarify cloudy water of a lake or river and make it clear especially if the sediment of colloidal particle is influence or disturb by water current. The approach by AC Electrokinetic phenomenon able to manipulate colloidal particles in a suspension. It can separate, trap or sort colloidal particle which made the phenomenon as possible reliable option for clarifying lake or river water from colloidal particles hence make it clear water. This work will simulate the process of clarification of colloidal suspension using AC Electrokinetic phenomenon in a lab. Electrodes were fabricated on Indium Tin Oxide (ITO) coated glass slide using laser etching technique. The electrode which poses unique geometry will be able to demonstrate electric field gradient as soon as it is introduced with electrical signal. Base on the surface potential of the colloids and the surface potential of the electrode, the colloids will be manipulated. This phenomenon is known as AC Electrokinetics. This can be regarded as guided sedimentation process. The trapped colloidal particle can be now easily extracted or remove from the water thus transform the water from cloudy to clear hence complete water clarification process.